Brave - McGowan, Rose, 1973- (HarperOne, an imprint of HarperCollinsPublishers, 2018)
"The surprising and captivating memoir and radical manifesto of one of the most controversial women in Hollywood--actress, activist, musician, director, and all-around feminist badass Rose McGowan"--